Examining the Impact of Fiscal Decentralization and Renewable Energy on CO2 Emissions: Insights from Pakistan - Faheem, Muhammad; Farooq, Fatima; Nousheen, Asma; Bashir, Furrukh (iRASD Journal of Economics, 2023)
The relevance of fiscal decentralization in environmental sustainability cannot be overstated. Some believe that fiscal decentralization is essential to long-term environmental health. However, to what extent fiscal decentralization (FSD) hinders or promotes ecological sustainability is a topic of heated debate. Knowing how fiscal decentralization impacts the environment is vital because it cannot be disregarded while working toward the Sustainable Development Goals of a clean environment and minimizing climate change. This study determines the relationship between FSD, NRE, RNE, GDP, and CO2 excretion, taking data from 2005 to 2021. We employed the ARDL model to investigate the association between study variables. The empirical findings show that fiscal decentralization, NRE, and GDP exert beneficial effects on CO2 exhalation and harm the environment, while RNE cleans the environment by decreasing CO2 outflow; yet, all study variables are positively connected with the ecological footprint. Based on the recommendations for Pakistan, It is suggested that policymakers and the government of Pakistan should allocate funds for green infrastructure to combat CO2 emissions.